Colloid Cyst of the Third Ventricle: A Case Report - Aleš Kopal; Jiří Preis; Leoš Ungermann; Edvard Ehler; Ivana Štětkářová (Acta Medica)
Colloid cyst of the third ventricle (CC) represents approximately 1% of intracranial tumours and 20% of intraventricular tumours. CC usually occurs between 20 and 50 years of age. During the first decade of life, it is diagnosed very rarely (1–2%). It can be most commonly found in the anterior part of the third ventricle at the foramen of Monro (1). It is often visualised during the computed tomography (CT) examination as a hyperdense focal lesion, it has variable change of the signal during magnetic resonance imaging (MRI) (2). CC has a benign character, however, a strategic position which may lead to acute hydrocephalus, intracranial hypertension syndrome, consciousness disorder, and even sudden death. This peracute hydrocephalus is an indication to an acute neurosurgical procedure (3).